5 Years in Juntos: New Evidence on the Program’s Short and Long-Term Impacts - Perova, Elizaveta (Economía, 2012)
This study presents results from a quantitative impact evaluation of the Conditional Cash Transfer (CCT) program, Juntos, in Peru. Using instrumental variable techniques, it estimates the overall impact of Juntos five years after its initial rollout and explores the differential impacts among beneficiaries according to the length of time they spent in the program. In so doing, the analysis explores whether it takes time for the program to make significant and sizable impacts; and whether some impacts change in magnitude the longer the beneficiaries spend in the program. The results seem to confirm both hypotheses: almost all indicators of interest are significantly higher among beneficiaries with longer treatment spells. However, in many cases these improvements are too small to be picked up in the analysis of overall effects, when beneficiaries are compared to non-beneficiaries. These findings suggest that while the program has a non negligible impact on welfare, there is room for improvement.